GREAT SILK WAY THE PEOPLE IN MYTHOLOGY THE DRAGON of your image ARTISTIC MIGRATION ISSUE (International conference on multidisciplinary science, 2024)
Medium in centuries of nations national plots and to his images Great silk the way thus constant migratory processes own from the beginning spent This process under the influence of the most famous has been mythological symbol dragon too to changes face held new content and forms occupation reached His number and quality in terms of change on the ground the most first of all spiritual superstructure – of nations religious and mythological ideas reason has been Such spiritual and literary of the foundation appear to be the dragon of the image to evolution constant way effect did In our article dragon of the image Great silk the way in mythology artistic to migration to meet issue about word we walk